Profile microsatellite mining of whole genome sequencing and transcriptomic assembly in dwarf and tall areca nut (Areca catechu) in Indonesia - MUHAMMAD ROIYAN ROMADHON; SOBIR SOBIR; WILLY BAYUARDI SUWARNO; DEDEN DERAJAT MATRA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Romadhon MR, Sobir, Suwarno WB, Matra DD. 2024. Profile microsatellite mining of whole genome sequencing and transcriptomic assembly in dwarf and tall areca nut (Areca catechu L.) in Indonesia. Biodiversitas 25: 1081-1088. Areca nut (Areca catechu L.) has high diversity in fruit shape and flowering time. Two superior varieties are commonly cultivated in Indonesia, namely Betara areca nut (tall) and Emas areca nut (dwarf). Molecular level diversity from genomic and transcriptome of areca nut data is available at NCBI, but not yet for Indonesian areca nut. The research compared the results of SSR with two method approaches to detect genetic diversity in the plants accurately. This study aimed to compare the SSR motifs of Betara areca nut and Emas areca nut varieties from whole genome sequencing and transcriptome assembly. The research was conducted at the Leuwikopo Seed Centre Laboratory of the IPB University, Bogor, Indonesia. The methods used are Whole Genome Sequencing (WGS) and transcriptome assembly. A total number of identified SSRs from WGS approach from Betara areca nut of 95 SSRs and Emas areca nut of 95 SSRs, while Betara areca nut SSRs from transcriptome assembly of 466 SSRs and Emas areca nut of 357 SSRs. The percentage of contigs and transcripts from Betara areca nut containing SSR was 7.43% and 4.22%, respectively, while Emas areca nut was 8.06% and 2.04%, respectively. AT is the dominant SSR motif in WGS, while the GA motif dominates the transcriptome assembly results.